1994
DOI: 10.1093/ajcn/59.3.626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistant starch on breath-hydrogen and methane excretion in healthy volunteers

Abstract: Colonic fermentation of dietary carbohydrates and fiber might produce a protective effect against the development of large bowel cancer. Resistant starch, ie, starch that escapes small bowel digestion, is a candidate fermentable substrate that has been hitherto little studied. We supplemented 19 healthy volunteers with 15 g native amylomaize (Hylon-VII) three times a day, containing 28 g type II resistant starch, or with dextrins as a placebo for 7 d in a crossover design. Pre-experimentally, 11 subjects regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Since the amount of fermentable carbohydrate is critical in avoiding problems with intolerance (Stone-Dorshow & Levitt, 1987), in this study, the threshold of gastrointestinal discomfort due to NUTRIOSE s FB was determined. Standard maltodextrin was used as placebo as reported earlier (Van Munster et al, 1994). During 6 days on 30, 60 or 80 g of NUTRIOSE s FB per day, the frequency of flatulence was higher than with the control treatment (same dose of maltodextrin).…”
Section: Discussionmentioning
confidence: 99%
“…Since the amount of fermentable carbohydrate is critical in avoiding problems with intolerance (Stone-Dorshow & Levitt, 1987), in this study, the threshold of gastrointestinal discomfort due to NUTRIOSE s FB was determined. Standard maltodextrin was used as placebo as reported earlier (Van Munster et al, 1994). During 6 days on 30, 60 or 80 g of NUTRIOSE s FB per day, the frequency of flatulence was higher than with the control treatment (same dose of maltodextrin).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intakes were evaluated by the dietitian using the 3-d food recall method, and the nutrient compositions were calculated according to the food composition table ( 9 ). Eight specific symptoms of GI were assessed using the questionnaire described by van Munster et al ( 10 ). The listed symptoms were: appetite, rumbling numbers and sound of GI tract, belching, flatulence, fecal smell, toilet habits, stool consistency and stool traits, while the degrees of GI discomfort were ranked from absent, mild, or moderate to severe ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…Eight specific symptoms of GI were assessed using the questionnaire described by van Munster et al ( 10 ). The listed symptoms were: appetite, rumbling numbers and sound of GI tract, belching, flatulence, fecal smell, toilet habits, stool consistency and stool traits, while the degrees of GI discomfort were ranked from absent, mild, or moderate to severe ( 10 ). Fasting venous blood of the subjects was withdrawn at baseline and week 8 by medical assistants.…”
Section: Methodsmentioning
confidence: 99%
“…The possible effect of the RS consumption on bowel transit time and the influence of RS on amino acids and vitamins showed no relationship of the fermentation with these parameters [108]. On the contrary, it was suggested that some RS types (RS2) would be able to improve calcium and magnesium absorption by enhancing mineral solubility in the cecum and/or large intestine due to acidification of the content induced by RS fermentation [89,122].…”
Section: Physiological Aspectsmentioning
confidence: 99%